Agro-tourism for sustainable development : willingness to pay, challenges and remedies from the perspective of Bangladesh - Sobhan, Sanjana; Zulfiqar, Farhad; Datta, Avishek; Himanshu, Sushil Kumar; Asian Development Bank-Japan Scholarship Program ADB-JSP (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Agro-tourism has evolved to be an emerging concept, drawing the interest of scholars and practitioners worldwide. By hosting and participating in this form of touristic on farm activities, farmers can diversify their revenue streams and help offset their declining agricultural earnings. However, Bangladesh failed to unlock opportunities and thrive in this booming sector despite the enormous potential. On the other hand, the research on agro-tourism{u2019}s challenges, remedies and willingness to pay in Bangladesh nexus, under a single comprehensive model has been left unaddressed. To fill the identified research gaps, this study aims to investigate the challenges of agro-tourism in order to propose viable remedies followed by an assessment of tourists{u2019} willingness to pay, based on Porsha, a sub-district of Naogaon, Bangladesh. With a mixed-method approach, this study employed both multistage and purposive sampling techniques for response gathering. The responses were collected from 398 tourists utilizing a structured questionnaire and 25 respondents from farmers, officials of Bangladesh Tourism Board and agricultural extension department, and local inhabitant, were interviewed through an in-person field survey. This study utilized an ordered probit regression model, multi-nominal regression model, SWOT analysis and a rank order for data estimation. The results depicted that visitors{u2019} education, income and interest in agro-tourism, affect their willingness to pay for visiting agro-tourism destinations. In the same vein, tourists with positive mindsets and higher levels of preference who encountered fewer problems while visiting agro-tourism sites, were more willing to pay. However, the findings from interviewees revealed that this industry has been confronted with several challenges despite emerging potential. By delineating possible remedies, this study articulates a more comprehensive understanding and contributes to the growth of this vibrant industry. Outlining policy implications such as amenities development in potential agro tourism area, marketing and promotional measures the study findings also offer useful directions for decision-makers, investors, researchers, farmers, tourists and other actors to help Bangladesh's agro-tourism industry flourish.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management in Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2023
Keywords: Agritourism -- Bangladesh -- Finance; Sustainable development -- Bangladesh -- Finance; Willingness to pay